2019
DOI: 10.1002/kin.21252
|View full text |Cite
|
Sign up to set email alerts
|

Reactive kinetics of carbon dioxide loaded aqueous blend of 2‐amino‐2‐ethyl‐1,3‐propanediol and piperazine using a pressure drop method

Abstract: In this study, a new pressure drop method has been used to investigate the kinetics of carbon dioxide reaction with aqueous blend of 2-amino-2-ethyl-1,3-propanediol (AEPD) with piperazine (PZ). The blending of a small amount of PZ with AEPD has a significant effect on the observed rate constant, k obs . It was observed that k obs values of the blend increased more than twice than the summation of k obs values of individual alkanolamines. The reaction kinetics in this study were modeled by assuming a termolecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…A small amount of PZ is necessary for the reaction to take place, while the addition of AEPD, an SHA, improves the system’s capacity for absorbing CO 2 . Ullah et al also experimentally studied the rate constant of the CO 2 reaction with blended amine absorbent AEPD-PZ with a new pressure drop method and obtained a similar conclusion. By addition of 0.1 mol/L PZ to AEPD, the observed rate constant, k 0 , was determined to be 8824.1 s –1 .…”
Section: Sterically Hindered Amine-based Absorbents: Roles In Co2 Abs...mentioning
confidence: 71%
“…A small amount of PZ is necessary for the reaction to take place, while the addition of AEPD, an SHA, improves the system’s capacity for absorbing CO 2 . Ullah et al also experimentally studied the rate constant of the CO 2 reaction with blended amine absorbent AEPD-PZ with a new pressure drop method and obtained a similar conclusion. By addition of 0.1 mol/L PZ to AEPD, the observed rate constant, k 0 , was determined to be 8824.1 s –1 .…”
Section: Sterically Hindered Amine-based Absorbents: Roles In Co2 Abs...mentioning
confidence: 71%
“…Piperazine (PZ) and its derivatives are commonly used promoters to enhance the CO 2 kinetics and absorption capacity [27][28][29][30]. This study proposes the use of biocatalysts to promote the CO 2 absorption-desorption process.…”
Section: Introductionmentioning
confidence: 99%
“…1), which is abundant and inexpensive renewable resource. Previously, we found that sterically hindered primary amines (AEPD and AMPD) have a high capacity for CO 2 capture but relatively slow reaction kinetics 26 . It has been studied that the reduced chemical reaction rate could be enhanced by adding highly active amine promoters, such as cyclic polyamines 27 .…”
Section: Introductionmentioning
confidence: 99%